Efficacy of intensive immunosuppression in exacerbated rheumatoid arthritis-associated interstitial lung disease. Issue 1 (2nd January 2017) - Ota, Mineto; Iwasaki, Yukiko; Harada, Hiroaki; Sasaki, Oh; Nagafuchi, Yasuo; Nakachi, Shinichiro; Sumitomo, Shuji; Shoda, Hirofumi; Tohma, Shigeto; Fujio, Keishi; Yamamoto, Kazuhiko
Abstract: Objectives : Acute or subacute exacerbations are recognized as a severe complication of rheumatoid arthritis-associated interstitial lung disease (RA-ILD). Nevertheless, the role of intensive immunosuppression in RA-ILD remains elusive. We attempted to evaluate the clinical characteristics and efficacy of immunosuppressive treatment in exacerbated RA-ILD. Methods : Clinical data, including respiratory function, imaging, treatment, and prognosis, were retrospectively collected for 17 patients with RA-ILD who required hospitalization at the University of Tokyo Hospital due to an acute exacerbation (12 patients) or subacute exacerbation (5 patients). Results : Patients with RA-ILD demonstrated a significantly higher titers of anticyclic citrullinated peptide antibodies compared with RA patients in Japanese Ninja registry, suggesting the role of adaptive immunity. Immunosuppressive treatment suppressed the deterioration of pulmonary functions with improved ground grass opacity and consolidation. In particular, in patients with less fibrosis on computed tomography (CT) images showed a better response to treatment. Although five patients treated with combination therapy, including cyclophosphamide, showed a severely decreased lung volume, these intensive therapies provided a good prognosis without fatalities for the average observation period of 474 days. Conclusions : Immunosuppressive therapy is effective for exacerbations of RA-ILD. For severe cases with low respiratory function, intensive therapy, including cyclophosphamide, has a potential to improve the prognosis.